Abstracts from the World Congress of Cardiology/Oriental Congress of Cardiology 2024 - The Editorial Team (Global Heart)
These are the top 30 abstracts from the combined 18th Oriental Congress of Cardiology together with the World Congress of Cardiology, held in June 2024. From 1950 to today, the World Heart Federation’s World Congress of Cardiology (WCC) has been a key event on the cardiovascular calendar, offering a global perspective on cardiovascular health and bringing together thousands of cardiology professionals from all over the world with one common goal: to reduce the global burden of cardiovascular disease and help people live longer, healthier lives.